2016
DOI: 10.1007/s11481-016-9660-2
|View full text |Cite
|
Sign up to set email alerts
|

Chemokine CCL2 enhances NMDA receptor-mediated excitatory postsynaptic current in rat hippocampal slices-a potential mechanism for HIV-1-associated neuropathy?

Abstract: Human immunodeficiency virus type 1 (HIV-1)-infected mononuclear phagocytes (brain macrophages and microglial cells) release proinflammatory cytokines and chemokines. Elevated levels of chemokine CC motif ligand 2 (CCL2, known previously as monocyte chemoattractant protein-1) have been detected in serum and cerebrospinal fluid (CSF) of HIV-1-infected individuals and the raised CCL2 in the CSF correlates with HIV-1-associated neurocognitive disorders. To understand how elevated CCL2 induces HIV-1-associated neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 45 publications
1
19
0
Order By: Relevance
“…Studies in animal models confirmed that alcohol induces elevated expression of CCL2 in the CNS (see Introduction). CCL2 has been shown to have neuronal actions in experimental preparations (Qin et al, 2005; van Gassen et al, 2005; Cho and Gruol, 2008; Edman et al, 2008; Jung et al, 2008; Guyon et al, 2009; You et al, 2010; Belkouch et al, 2011; Kao et al, 2012; Zhou et al, 2016). These findings raise the possibility that effects of CCL2 may play a role in the CNS actions of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in animal models confirmed that alcohol induces elevated expression of CCL2 in the CNS (see Introduction). CCL2 has been shown to have neuronal actions in experimental preparations (Qin et al, 2005; van Gassen et al, 2005; Cho and Gruol, 2008; Edman et al, 2008; Jung et al, 2008; Guyon et al, 2009; You et al, 2010; Belkouch et al, 2011; Kao et al, 2012; Zhou et al, 2016). These findings raise the possibility that effects of CCL2 may play a role in the CNS actions of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…The production of CCL2 by neurons during acute encephalitis may play a role in more than just leukocyte recruitment. For example, hippocampal neurons express CCR2 [21] and CCL2 directly enhances both NMDA receptor-and AMPA receptor-mediated excitatory postsynaptic potentials [30]. This suggests that the earliest stages of hippocampal circuit dysregulation associated with acute TMEV infection may be triggered locally by neuronal CCL2 acting in a autocrine fashion [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that HIV also affects many other ion channels and receptors that likely participate in pathogenic processes related to HAND and that may also be affected in the current model/treatment regimen. For example, HIV reduces inhibitory GABA neurotransmission (Buzhdygan et al, 2016) and enhances the activity of another ionotropic glutamate receptor, the AMPAR (Epstein, 1998; Zhou et al, 2016). Reduced inhibitory neurotransmission (GABA) and increased excitatory stimulation of glutamatergic ionotropic receptors (AMPA and NMDAR) also contributes to membrane depolarizations that, if large enough, could ultimately activate VGCCs, including the L-channel, and promote excessive Ca 2+ influx.…”
Section: Discussionmentioning
confidence: 99%